1996
DOI: 10.2307/2410652
|View full text |Cite
|
Sign up to set email alerts
|

Drought Stress and Inbreeding Depression in Lychnis flos-cuculi (Caryophyllaceae)

Abstract: Interactions between drought stress and inbreeding depression were studied in Lychnis jlos-cuculi. Four inbreeding levels (F = 0, 0.25, 0.50 and 0.75), and three watering treatments were used. Performance was scored for germination rate and proportion, survival, plant size, proportion of plants flowering, flowering date, stem height, number of flowers, flower size, anther weight, fruiting proportion and number of capsules. Multiplicative fitness values were estimated from these traits. Inbreeding affected most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
65
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 18 publications
6
65
2
Order By: Relevance
“…The negative effects of low pollen diversity on offspring performance were not significantly enhanced under stressful environmental conditions in our study. By comparison, other studies (Hauser & Loeschke, 1996;Dahlgaard & Loeschke, 1997) found stronger inbreeding depression under stressful environmental conditions. This suggests that even if purging has occurred under environmental conditions closer to the species' optimum, additional inbreeding depression is still expressed under novel conditions (Bijlsma et al, 1999).…”
Section: Effects Of Low Vs High Pollen Diversitycontrasting
confidence: 77%
“…The negative effects of low pollen diversity on offspring performance were not significantly enhanced under stressful environmental conditions in our study. By comparison, other studies (Hauser & Loeschke, 1996;Dahlgaard & Loeschke, 1997) found stronger inbreeding depression under stressful environmental conditions. This suggests that even if purging has occurred under environmental conditions closer to the species' optimum, additional inbreeding depression is still expressed under novel conditions (Bijlsma et al, 1999).…”
Section: Effects Of Low Vs High Pollen Diversitycontrasting
confidence: 77%
“…Inbreeding depression may increase with environmental harshness over applies to a range of stress levels (Komaki, 1982;Levin, 1984;Pray ci' al., 1994;Hauser & Loeschcke, 1996). However, when a stress is extremely severe, differences in survival among inbreeding groups may be diminished when the stress level is elevated further (Dahlgaard et a!., 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Inbreeding usually reduces mean fitness relative to outbred individuals (inbreeding depression), but there is conflicting evidence on whether inbreeding depression is exaggerated in stressful environments (relationship supported: Hauser & Loeschke (1996), Bijlsma et al (1999); relationship unsupported: Dahlgaard & Loeschke (1997), Dahlgaard & Hoffmann (2000)). …”
Section: Introductionmentioning
confidence: 99%